Plantain Peels Powder, Burnt Palm Head Powder and Commercial Sodium Hydroxide as Additives for Water Based Drilling Mud - JP Peretomode (Journal of Applied Sciences and Environmental Management)
Drilling operation efficiency is enhanced by the application of drilling mud constituted with suitable additives. This work investigates the use of locally sourced plantain peels powder (PPP) and burnt palm head sponge powder (BPHSP) in comparison with the use of commercial sodium hydroxide (NaOH) as additives for the enhancement of the pH and rheological properties of water-based mud. The water-based mud samples with and without various amounts (1.0 – 5.0 g) of PPP, BPHSP and commercial NaOH, respectively. Analyses of the results revealed that the pH and rheological properties (apparent viscosity, plastic viscosity and yield point) of the formulated waterbased mud were relatively enhanced with the respective use of the commercial NaOH, BPHSP and PPP as additives. The pH, apparent viscosity and yield point respectively increased with increase in the quantity of each of the added additives (commercial NaOH, BPHSP and PPP). The commercial NaOH had the highest percentage of improvement on the mud pH with 22.2 – 50%, followed by that of BPHSP (16.7 – 44.4%) and PPP (11.1 – 33.3%), respectively. Therefore, commercial sodium hydroxide, burnt palm head sponge ash powder and plantain peels powder can respectively be used as additives to enhance or improve the pH and rheological properties (viscosity and yield point) of water-based mud.